Unveiling the Multifaceted Implications of Artificial Intelligence Adoption on Sustainable Development: Perspectives and Hurdles - Subramaniam, Radhakrishnan; Palakkeel, Prashobhan; Arunmozhi, Manimuthu; S., Manikandan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The rapid evolution of information technology continues to exert significant disruptive forces on various societal facets. Amidst this transformation, digital adoption has emerged as a potent driver reshaping social well-being and economic landscapes. While prior research has predominantly examined socioeconomic elements within the realm of sustainable development, our study uniquely focuses on unraveling the intricate interplay between information technology and sustainable progress. This research endeavors to investigate the multifaceted impacts of digital adoption, shedding light on its profound influence across diverse dimensions linked to the Sustainable Development Goals. Specifically, we delve into critical aspects such as alcoholism, unemployment, literacy rates, research and development expenditure, GDP growth, and the influx of personal remittances—an often-overlooked facet of economic vitality. Our comprehensive analysis unveils a panorama where digital adoption distinctly contributes to positive advances in literacy levels, economic prosperity facilitated by migrant remittances and stimulation of research fostering innovation. However, the transformative journey of digital adoption also casts its shadow, giving rise to challenges in the realm of sustainable development. Notably, it exacerbates issues like bolstering GDP expansion, alcoholism and unemployment. The advent of digital adoption, with its inherent capacity to enhance information symmetry, paradoxically coincides with an upsurge in alcohol consumption. Moreover, the proliferation of information technology, particularly in the form of IT capital, precipitates workforce displacement, necessitating strategic interventions for skills redevelopment to ensure sustainable employment—a crucial imperative. In essence, this study augments existing knowledge by offering nuanced insights of paramount importance to policymakers, societal stakeholders, and organizations alike. By illuminating the potential pitfalls of digital adoption, notably the perils of unemployment and alcoholism, our findings underscore the urgency of implementing mitigation strategies. Notwithstanding these challenges, our research casts a positive glow, guiding strategic investment decisions at the macroeconomic, social, and organizational echelons. In conclusion, this paper navigates the intricate terrain of information technology's integration into society, unearthing both its promising prospects and inherent challenges. By accentuating the multifaceted relationship between digital adoption and sustainable development, our study enriches the discourse with vital perspectives, thus facilitating informed choices for a digitally empowered future.